Classification and mapping of tumour-infiltrating lymphocytes (TILs) in lung adenocarcinoma and lung squamous cell carcinoma - Hadjinicolaou, Constantinos; Justus Liebig University Giessen (My University, 2019)
Lung cancer is the most frequent and one of the deadliest types of cancer. The goal of this study was to determine the type of tumour-infiltrating lymphocytes, map them and show which types of lymphocytes predominate in the immune response. In the end, an attempt was made to find correlations between the obtained results. Furthermore, the tumour-infiltrating lymphocytes were stained to find the percentage of expression of PD-1 surface protein.
Keywords: ddc:610